Immunonutrition for Pediatric Patients With Cow's Milk Allergy: How Early Interventions Could Impact Long-Term Outcomes - Carucci, Laura; Coppola, Serena; Luzzetti, Anna; Voto, Luana; Giglio, Veronica; Paparo, Lorella; Nocerino, Rita; Berni Canani, Roberto (Frontiers in Allergy, 2021)
Cow’s milk allergy (CMA) is one of the most common food allergies and one of the main causes of food-induced anaphylaxis in the pediatric age. Moreover, up to 45% of CMA children develop other atopic manifestations later in the life, a phenomenon commonly named atopic march. Thus, CMA imposes a significant cost to the health care systems as well as to the families, and it emerged as one of the most expensive allergic diseases. The ImmunoNutrition strategy builds its foundation on the ability of selected dietary factors to modulate the immune system development and function. Recent studies highlighted the potential of ImmunoNutrition in the management of CMA. This review is focused on the mechanisms and long-term clinical outcomes of the ImmunoNutrition approach in children with CMA.